Antiviral and antibacterial potential of electrosprayed PVA/PLGA nanoparticles loaded with chlorogenic acid for the management of coronavirus and Pseudomonas aeruginosa lung infection - Asmaa Saleh; Dalia H. Abdelkader; Thanaa A. El-Masry; Duaa Eliwa; Badriyah Alotaibi; Walaa A. Negm; Engy Elekhnawy (Artificial Cells, Nanomedicine, and Biotechnology, 2023)
AbstractRespiratory tract infections are a common cause of morbidity and mortality globally. The current paper aims to treat this respiratory disorder. Therefore, we elucidated the phytochemical profile of Euphorbia milii flowers and isolated chlorogenic acid (CGA) for the first time. The electrospraying technique was utilized to prepare CGA nanoparticles in polyvinyl alcohol (PVA)/PLGA polymeric matrix. Complete in vitro characterizations were performed to determine particle size, polydispersity index (PDI), zeta potential, loading efficiency (LE), scanning electron microscopy and in vitro release study. The optimum formula (F2) with a particle size (454.36 ± 36.74 nm), a surface charge (–4.56 ± 0.84 mV), % of LE (80.23 ± 5.74), an initial burst (29.46 ± 4.79) and % cumulative release (97.42 ± 4.72) were chosen for further activities. In the murine lung infection model, PVA/PLGA NPs loaded with CGA (F2) demonstrated in vivo antibacterial activity against Pseudomonas aeruginosa. Using a plaque assay, the in vitro antiviral activity was investigated. The F2 exhibited antiviral activity against coronavirus (HCoV-229E) and (Middle East respiratory syndrome coronavirus (MERS-CoV), NRCEHKU270). The IC50 of F2 against HCoV-229E and MERS-CoV was 170 ± 1.1 and 223 ± 0.88 µg/mL, respectively. The values of IC50 of F2 were significantly lower (p < .05) than that of free CGA. Therefore, the encapsulation of CGA into electrospray PVA/PLGA NPs would be a promising tool as an antimicrobial agent.